Impact of parental perinatal depressive and anxiety symptoms on infant development and health: A cohort study in east and west coasts of Malaysia - Nasreen, Hashima E (2019)
In low- and middle-income countries, research on antepartum psychiatric morbidities investigating simultaneously both antepartum depressive and anxiety symptoms (ADS and AAS) in women and men is lacking. Prior evidence linking maternal ADS and AAS with adverse birth outcome and caesarean section (CS) or instrumental delivery is conflicting. There is no research on the association between maternal mental disorders and adverse birth outcomes and mode of delivery in Malaysia. This study estimated the prevalence of depressive, anxiety and co-morbid symptoms, explored their associated factors and investigated the independent effect of maternal ADS and AAS on newborn’s low birth weight (LBW), preterm birth (PTB) and CS or instrumental delivery among women in east and west coasts of Malaysia. A prospective cohort study of 911 women and 587 husbands was carried out 10 health clinics of two states in east and west coasts of Malaysia. Participants were recruited at the third trimester of pregnancy who were followed up at birth, 2–3 months and 6 months postpartum. Baseline data were measured at the third trimester of pregnancy on ADS, AAS, socioeconomic condition, anthropometric status, reproductive history and intimate partner violence. Birth outcomes and mode of delivery were determined at delivery. The validated Malay version of Edinburgh Postnatal Depression Scale, and the anxiety scale of Depression, Anxiety and Stress Scale were used to measure depressive and anxiety symptoms. Multiple logistic regression analyses identified the determinants of antepartum depressive and anxiety symptoms (ADS and AAS) and multiple Cox’s regressions assessed the association between ADS and AAS and LBW, PTB and CS or instrumental delivery. The prevalence of ADS was 12.2% in women and 8.4% in men, AAS 28.8% in women and 13.3% in men, and comorbid symptoms 8.0% in women and 4.0% in men. Social/family support, stressful life events, intimate partner violence and poor relationship with husbands (women only), depression in earlier pregnancy, living in a rental house and sex preference for the unborn child (men only) were found to be associated with ADS. The determinants for AAS were unemployment, living with parents/in-laws, restrictions during pregnancy and poor relationship with husbands for women, and stressful life events for both women and men. ADS was significantly associated with an increased risk of giving birth to LBW babies in both east coast (RR = 3.64; 95% CI 1.79–7.40) and west coast (RR = 3.82; 95% CI 1.86–7.84), but not with PTB. AAS was associated with increased risk of both LBW (RR = 2.47; 95% CI 1.39–4.38) and PTB (RR = 2.49; 95% CI 1.16–5.36) in the east coast, but not in west coast. The risk of CS or instrumental delivery was evident among women with ADS (RR = 2.44; 95% CI 1.48–4.03) in west coast only. Likewise, maternal postpartum depressive symptoms predicted infant underweight and ADS predicted infant stunting. Therefore, policies aimed at detection and management of ADS and AAS during antenatal check-up in health clinics may help improve birth outcomes and reduce obstetric interventions. Administration of couple-based screening and referral programme during antenatal check-up should be universal practices to identify and treat the psychiatric morbidities.